2016
DOI: 10.4236/abb.2016.71003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Human Hair Induced by UV- and Gamma Irradiation

Abstract: The effect of UV-and 137 Cs gamma radiation on the structural and chemical integrity of human hair was studied to determine the feasibility of using human hair as a non-invasive biomarker of radiation exposure to ionized gamma-and non-ionized UV-radiation. Steady state tryptophan (Trp) fluorescence and chemical analytical methods were used to evaluate the molecular integrity of Trp fluorophores and SH-groups in hair proteins and to assess the radiation induced damage quantitatively. It was found that human hai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…The prediction of a flat dose-response at high gamma radiation doses 39 of up to 200 Gy is not found in present work, the tryptophan being incompletely damaged or depleted. The damage due to gamma irradiation has been reported to be significantly reduced in dehydrated hair with 10–30% of water content relative to other biological samples such as viable epidermis of the skin with 70% water content 39 41 .
Figure 6 PL spectra of hair samples subjected to gamma irradiation doses ranging from 0 to 200 Gy.
…”
Section: Resultscontrasting
confidence: 87%
See 2 more Smart Citations
“…The prediction of a flat dose-response at high gamma radiation doses 39 of up to 200 Gy is not found in present work, the tryptophan being incompletely damaged or depleted. The damage due to gamma irradiation has been reported to be significantly reduced in dehydrated hair with 10–30% of water content relative to other biological samples such as viable epidermis of the skin with 70% water content 39 41 .
Figure 6 PL spectra of hair samples subjected to gamma irradiation doses ranging from 0 to 200 Gy.
…”
Section: Resultscontrasting
confidence: 87%
“…Of note is that the tryptophan concentration in hair varies with age (being greater in first few years of life, 1–5 years, and highest in aging subjects 61 years), sex (higher in males), and hair colour (highest in white and grey hair, followed by black and brown hair) 38 . Figure 7 c shows the dose-response curve for doses of 10 Gy and beyond, fitted to a logarithmic function, in which the photoluminescence from the hair decreases with increasing dose ( ), evidence of hair damage being associated with the reaction of free radicals and direct deposition of energy 39 . Conversely to the situation presented for irradiations for doses from 0 to 10 Gy, a downward trend in hair fluorescence for the same dose range was observed 39 , delivered in this case by (662 keV; LET ), obtained at an emission wavelength of 335 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that exposure to ionizing gamma radiation cleaves the disulfide bonds and decomposes amino acids in keratin, cysteine hair leading to the formation of cysteic acid, CySO3 H.The numerous disulfide bonds formed by cysteine are responsible for the great stability of keratin and both keratin and cysteine are very reactive, can easily be reduced, oxidized, and hydrolyzed . [13] It is worth to mention that both of heat and irradiation produced decomposition of tryptophan residues to kynurenine type oxidation products. [14][15][16] Stress of heat and/or irradiation stimulated the pro-inflammatory cytokines, [17] which can further activate kynurenine pathway through the induction of indole amine 2, 3dioxygenase and tryptophan 2, 3-dioxygenase enzymes.…”
Section: Discussionmentioning
confidence: 99%